The Study of Correlation Between Heavy Metal Levels in Environment and Autism Case in Samarinda and Bantul - Hasdam, Andi Sofyan; Hasim; Sulaeman, Ahmad; Hasan Machfoed, Moh. (Media Kesehatan Masyarakat Indonesia, 2020)
Autism is a disorder of pervasive development in children, which until now, the exact cause is unknown. The strongest allegations are genetic and environmental factors, especially heavy metals. This study aims to look the relationship between the occurrence of heavy metals pollution with the autism cases in Samarinda and Bantul. This study was carried out by measuring the levels of heavy metals in fish, vegetables, water and soil and also hair of 30 autistic children and 10 control children in Samarinda and 30 autism 4 control in Bantul.All samples were measured their heavy metal content (As, Hg, Cd, Pb) at The Central Nuclear Applied Science and Technology Laboratory in Bandung. The result compares with the standard value and were found that the samples was exceeding the heavy metals value in Samarinda is Arsenic in fish, lead in fish. While in Bantul, Mercury in fish, mercury in vegetable and lead in vegetable. In the hair samples result, the level of arsenic, mercury and lead were higher in autism children compared to controls in Samarinda, while in Bantul only mercury and lead levels are higher in hair of autism children than controls. Cadmium levelswere no difference between autistic and control hair both in Samarinda and Bantul.